Farewell to Bright-Line: A Guide to Reporting Quantitative Results Without the S-Word - Cummins, Kevin M.; Marks, Charles (Frontiers in Psychology, 2020)
Recent calls to end the practice of categorizing findings based on statistical significance have focused on what not to do. Practitioners who subscribe to the conceptual basis behind these calls may be unaccustomed to presenting results in the nuanced and integrative manner that has been recommended as an alternative. This alternative is often presented as a vague proposal. Here we provide practical guidance and examples for adopting a research evaluation posture and communication style that operates without bright-line significance testing. Characteristics of presentation of results based on conventional significance testing are presented. Guidelines for writing results without the use of significance testing are then provided. Examples of conventional styles for communicating results are presented. These examples are then modified to conform to recent recommendations. These examples demonstrate that basic modifications to written scientific communications can increase the information content of scientific reports without a loss of rigor. The adoption of alternative approaches to results presentations can help researchers comply with multiple recommendations and standards for the communication and reporting of statistics in the psychological sciences.